شروڤه‌كرن و چاره‌سه‌ریا شاشیێن خالبه‌ندیێ و رێنڤیسێ د زمانێ راگه‌هاندنێدا (رۆژناما ئه‌ڤرۆ وه‌ك نموونه)‌ - MOHAMMAD, SULAIMAN HISHYAR; RAJAB, SULAIMAN ISMAIL (Journal of Duhok University, 2020)
The lack of a unified dictation system among all classes of society today created a majorproblem for the Kurdish dictation system, especially in the field of education, and this problemappears more clearly in the form and technique of writing. The lack of a strong linguistic centerto supervise this thing facilitated that each party, according to their personal information,change the form of writing and use it according to their desire, or that the language of the mediaoften does not pay attention to the language and the laws of the language, and the goal is thattheir main purpose is to deliver the message to readers in a simple and fast manner. Therefore,the language side is neglected, even though the language of the media is a powerful tool forpreserving and developing the language because in the easiest way, all parts of society canbenefit from new words and terms provided that this language is free of grammatical andspelling errors. That is why this language must be analyzed academically and accurately, andacceptable and normative examples must be shown and become a basis for the development ofthe language. This research is an academic scientific attempt to determine the correct andscientific principles of a correct spelling system in terms of dictation and technique